The Paleogene record of Himalayan erosion; Burma and Bangladesh - Najman, Yani; Allen, Ruth; Bickle, Mike; BouDagher-Fadel, Marcelle; Carter, Andy; Garzanti, Eduardo; Paul, Maxence; Wijbrans, Jan; Willett, Ed; Oliver, Grahame; et al. (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1288 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.94